Dynamic early recruitment of GAK–Hsc70 regulates coated pit maturation - Zhangping He; Peiyao Zuo; Peiliu Xu; Haozhi Yuan; Madhura Bhave; Xiangying Wei; Ziyan Yang; Lu Han; Sandra L. Schmid; Zhiming Chen (Proceedings of the National Academy of Sciences, 2025)
Clathrin-mediated endocytosis (CME) begins with the assembly of clathrin onto the plasma membrane. These structures grow and stabilize to form clathrin-coated pits (CCPs), which invaginate and accumulate cargo. Finally, through membrane fission, CCPs detach to form clathrin-coated vesicles (CCVs). Mechanisms governing the transition of CCPs from flat-to-curved structures have been a matter of debate. GAK and its chaperone protein, Hsc70, are well known to mediate clathrin release from CCVs, and several studies have observed a late burst of GAK recruitment as CCVs form. Other studies have proposed that early recruitment of GAK–Hsc70 could function to provide the necessary energy source to remodel nascent flat clathrin lattices, replacing hexagons with pentagons and enabling a gain of curvature and invagination of the growing CCP; however, direct functional evidence is lacking. Here, we show that GAK knockdown inhibits CCP stabilization and invagination. Furthermore, mutations in the J domain of GAK that abolish Hsc70 recruitment to and activation at CCPs lead to the accumulation of GAK at CCPs, hinder CCP stabilization and invagination, and result in a striking increase in the proportion of highly transient, abortive CCPs. These findings support the hypothesis that GAK–Hsc70 promotes the turnover and remodeling of nascent clathrin assemblies required for curvature development during CME.